Does Socioemotional Wealth Matter for Competitive Advantage? A Case of Polish Family Businesses - Katarzyna Bratnicka-Myśliwiec; Martyna Wronka-Pośpiech; Tomasz Ingram (Journal of Entrepreneurship, Management and Innovation)
A growing body of research is concerned with how family businesses achieve competitive advantage, yet unique qualities that distinguish family firms and non-family firms are sometimes overlooked. In our study, we argue that socioemotional wealth (SEW) may trigger or limit family firms’ strategic initiatives that ultimately shape their competitive advantage. Therefore, in our study of 193 Polish family firms, we investigate how (SEW) and a firm’s competitive advantage are associated with a family firm context. Our research results reveal that, indeed, (SEW) and competitive advantage are partially associated and SEW can be regarded as an important strategic antecedent to firm performance